THE INFLUENCE OF PUSH UP TRAINING ON THE RESULTS OF THROW IN - RS, Arjun Nurzalla; Destriani, Destriani; Victorian, Achmad Richard (Journal Physical Education, Health and Recreation, 2023)
This study aims to determine the effect of push-up training on the long throw-in results of U-14 to U-16 SSB players Ogan Ilir 32. The method used in this study was. The research design used was One Group Pretest-Posttest Design. This sampling uses a total population sampling technique with a total sample of 30 players. The instrument of this research is the throw-in technique test. From the results of processing and analyzing data using the data normality test and testing the hypothesis with the T test formula, that the push up exercise has an effect on increasing the distance in the results of the throw-in in soccer players. This can be seen from the results of data analysis through the calculation of the t test formula with the criteria t count is greater than t table (13.730 Ëƒ 1.70) with a confidence level of 0.95 (Î± = 0.05) and the number of samples (N = 30). Push-up exercises have an effect on increasing the results of throw-in for U-14 to U-16 SSB players Ogan Ilir 32.